Epistemologi Tafsir bi al-ma’tsur dalam Kitab Al-Durr al-Manṡūr: Kritik atas Otoritas Riwayat dan Relevansinya dalam Studi Tafsir Kontemporer - Muhammad Baharuddin; Andi Abdul Hamzah; Abdul Rahman Sakka (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2026)
Tafsīr bi al-Ma’ṡūr has traditionally been regarded as the most authoritative approach to Qur'anic exegesis because it relies on transmitted reports (naql) from the Qur'an, the Prophet, the Companions, and the Successors. This study examines the epistemological foundation of tafsīr bi al-Ma’ṡūr in Jalāl al-Dīn al-Suyūṭī’s Al-Durr al-Manṡūr, evaluates the authority of its transmitted reports, and explores its relevance to contemporary Qur'anic studies. Using a qualitative library research approach with descriptive-analytical and critical methods, the study analyzes Al-Durr al-Manṡūr alongside classical and recent literature (2020–2026). Data were analyzed through the Miles and Huberman interactive model, supported by riwāyah and dirāyah criticism. The findings indicate that although Al-Durr al-Manṡūr prioritizes transmitted knowledge as the foundation of Qur'anic interpretation, its omission of complete isnād, lack of authenticity classification, and inclusion of Isrā’īliyyāt narratives weaken its epistemological authority if accepted uncritically. The study concludes that the work should be treated as a valuable repository of exegetical traditions requiring rigorous verification through ḥadīth and tafsīr criticism to maintain its relevance and methodological credibility in contemporary Qur'anic scholarship.